2019
DOI: 10.3390/su11082266
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Biomass Waste into Sustainable Organic Fertilizers

Abstract: The management of solid waste presents a challenge for developing countries as thegeneration of waste is increasing at a rapid and alarming rate. Much awareness towards thesustainability and technological advances for solid waste management has been implemented toreduce the generation of unnecessary waste. The recycling of this waste is being applied to producevaluable organic matter, which can be used as fertilizers or amendments to improve the soil structure.This review studies the sustainable transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(91 citation statements)
references
References 80 publications
1
83
0
7
Order By: Relevance
“…Biofertilizers are known to play an important role in sustaining soil fertility and condition, as well as crop production by mobilizing the available nutrients with their biological activities [5,22,89]. Additionally, Li et al [50] and Ansari and Mahmood [90] reported that an integration of organic compost and biofertilizers is a widely recognized INM strategy to improve several soil physical, chemical, and biological proprieties.…”
Section: Impacts Of Biofertilizer Treatments On Different Soil Propermentioning
confidence: 99%
See 2 more Smart Citations
“…Biofertilizers are known to play an important role in sustaining soil fertility and condition, as well as crop production by mobilizing the available nutrients with their biological activities [5,22,89]. Additionally, Li et al [50] and Ansari and Mahmood [90] reported that an integration of organic compost and biofertilizers is a widely recognized INM strategy to improve several soil physical, chemical, and biological proprieties.…”
Section: Impacts Of Biofertilizer Treatments On Different Soil Propermentioning
confidence: 99%
“…There are complex factors affecting nutrient balance in soil, especially the nutrients that are removed from it. In arid conditions, frequent soil tillage, removal of crop residues, and extensive use of synthetic fertilizers, along with high temperature and scarce rainfall, are the most dominant factors that usually result in progressive deterioration in soil fertility and quality by rapidly decreasing soil organic matter (SOM) [3][4][5]. A significant SOM decline causes a considerable deterioration of a range of chemical, physical, and biological soil characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vermicomposting, which is the biodegradation of organic wastes using earthworms and microorganisms [8][9][10], has been reported as an effective and relatively inexpensive cattle manure management technology [11,12]. The technology is also considered a bioecologically sustainable process in which renewable biological resources with an added value are produced [13].…”
Section: Introductionmentioning
confidence: 99%
“…So, the farmers dumped the biomass on road sides or burnt or left in to situ causing detrimental impact on environment. The management of solid waste presents a challenge for developing countries as the generation of waste is increasing at a rapid and alarming rate [12].…”
Section: Introductionmentioning
confidence: 99%